A novel chaos based optical cryptosystem for multiple images using DNA-blend and gyrator transform. (March 2021) - Chen, Hang; Liu, Zhengjun; Tanougast, Camel; Liu, Feifei; Blondel, Walter
Highlights: Eight kinds of deoxyribonucleic acid (DNA) matrices in binary form are also considered is introduced for multispectral image encryption in gyrator domains. The proposed cryptosystem performances well when facing the potential attacks since some high sensitive parameters are embedding in the encryption process. Some parameters in the encryption process are regarded as the extra keys to improve the security of the cryptosystem. Abstract: In this paper, a novel optical encryption algorithm for multiple images based on chaos and DNA-blend in gyrator transform domain is proposed. Firstly, the multispectral image is divided into eight parts regularly. Subsequently the pixel positions of the blocked images are scrambled according to the pixel values of the chaotic sequences generated by 4D Lorenz system. Furthermore, eight kinds of deoxyribonucleic acid (DNA) matrices in binary form are also considered and utilized among the eight blocked fragments. Finally, the scrambled images are encoded and transformed in optical gyrator transform light field and the ciphertext is scrambled by Arnold transform to enhance the security. The proposed cryptosystem can be implemented by an electro-optical hybrid setup. Some parameters of the chaos system and gyrator transform serves as the extra keys of the encryption scheme. Some numerical simulations are implemented to testify the validity and robustness of the proposed cryptosystem for multiple images.